Evaluación de aplicaciones foliares de calcio, magnesio, zinc y boro en el cultivo del banano - Rodriguez Granda, Dayana Norely (Machala : Universidad Técnica de Machala, 2021)
The present work was developed in areas of the Santa Inés farm located in the Faculty of Agricultural Sciences belonging to the Technical University of Machala and its objective was to evaluate the effect of foliar fertilizers (Ca, B, Mg, Zn) by measuring growth variables of the banana crop, clone Williams, in order to assess the effect on the growth and development of the crop. The banana (Musa x paradisiaca L.) is a perennial crop whose fruit is highly marketed and demanded worldwide, since it has nutritional and mineral components in its pulp, which makes it widely used as a staple food. The banana crop is one of the most important economic sectors in Ecuador, covering more than a third of the world's banana exports historically. It has proven to have a competitive advantage in production, standing out for having a high quality fruit and exquisite flavor, which is why the country has become the largest exporter worldwide. Due to the low fertility of some soils it is not possible to obtain adequate growth and yields. Foliar fertilizers are important due to their easy absorption and allow us to correct nutritional deficiencies quickly and efficiently. The experimental design used was a completely randomized block design with 4 treatments and 3 replications, each treatment as follows: T1, concentrated suspensions, composed of 20cc. Calctrac, Bortrac, Zintrac, Magtrac + 1.5 l. Water; T2, chelated, (20cc Fertiquel (Ca, B, Zn, Mg) + 1.5 l. Water); T3 (20cc Banatrel + 1.5 l. Water) and T4 control. The variables evaluated were: leaf emission (EF) number of leaves emitted weekly, leaf area (AF) the third youngest leaf was evaluated, height of the mother plant (AM) measured from the base to the third youngest leaf, height of the daughter plant (AH), stem of the mother plant (FM), stem of the daughter plant (FH). For statistical processing of the data, the IBM - SPSS version 22 program was used. The data obtained from the field evaluation were organized according to their corresponding variable and treatment. An exploratory data analysis was performed to determine the existence or absence of outliers that could affect the representativeness of the sample. The Shapiro Wilk test and Levene's test were then applied to corroborate the assumptions of normality and homoscedasticity, respectively. Once the statistical assumptions were met, the existence of significant differences was determined through a parametric test, such as the one-factor analysis of variance, which allowed identifying the existing differences through Duncan's post hoc tests with 99% reliability. The results obtained show that the foliar fertilizer corresponding to treatment T4 Banatrel showed the best results in all the variables evaluated with average values of 330.22 cm, 66 cm, 33.88 cm, 0.81 and 6.81 m2 in height of mother plant, stem of mother plant, stem of daughter plant, leaf emission and leaf area, respectively.
El presente trabajo se desarrollo en áreas de la granja Santa Inés ubicada en la Facultad de Ciencias Agropecuarias perteneciente a la Universidad Técnica de Machala y tuvo como objetivo evaluar el efecto de fertilizantes foliares (Ca, B, Mg, Zn) mediante la medición de variables de crecimiento del cultivo de banano, clon Williams, con la finalidad de valorar el efecto en el crecimiento y desarrollo del cultivo. El banano (Musa x paradisiaca L.) es un cultivo perenne cuyo fruto es muy comercializado y solicitado a nivel mundial, ya que posee componentes nutricionales y minerales en su pulpa, lo que hace sea muy utilizado como alimento de primera necesidad. El cultivo de banano es uno de los rubros económicos más importantes del Ecuador, cubre más de la tercera parte de las exportaciones mundiales de banano históricamente. Ha demostrado tener una ventaja competitiva en producción, destacándose por tener una fruta de alta calidad y exquisito sabor, razón por la cual se ha convertido el país en el mayor exportador a nivel mundial. Debido a la baja fertilidad de algunos suelos no es posible obtener crecimientos y rendimientos adecuado. Los fertilizantes foliares resultan importantes debido a su fácil absorción y nos permiten corregir deficiencias nutricionales de manera rápida y eficaz. El diseño experimental utilizado fue de bloques completamente al azar con 4 tratamientos y 3 repeticiones, cada tratamiento conformado de la siguiente manera: T1, suspensiones concentradas, compuesto por 20cc. Calctrac, Bortrac, Zintrac, Magtrac + 1.5 l. Agua; T2, quelatados, (20cc Fertiquel (Ca, B, Zn, Mg) + 1.5 l. Agua); T3 (20cc. Banatrel + 1.5 l. Agua) y T4 testigo. Las variables evaluadas fueron: emisión foliar (EF) número de hojas emitidas semanalmente, área foliar (AF) se evaluó la tercera hoja más joven, altura de la planta madre (AM) medida desde la base hasta la tercera hoja más joven , altura de la planta hijo (AH), fuste de la planta madre (FM), fuste de la planta hijo (FH). Para el procesamiento estadístico de los datos se utilizó el programa IBM - SPSS versión 22. Los datos obtenidos de la evaluación de campo se organizaron según su variable y tratamiento correspondiente. Se realizó un análisis exploratorio de datos para determinar la existencia o ausencia de valores atípicos que puedan incidir en la representatividad de la muestra. Después se aplicó la prueba de Shapiro Wilk y el Test de Levene para corroborar los supuestos de normalidad y homocedasticidad respectivamente. Cumplido los supuestos estadísticos, se determinó la existencia de diferencias significativas a través de una prueba paramétrica, como el análisis de varianza unifactorial, lo que permitió identificar las diferencias existentes a través de pruebas post hoc de Duncan con un 99 % de confiabilidad. Los resultados obtenidos demuestran que el fertilizante foliar correspondiente al tratamiento T4 Banatrel mostro los mejores resultados en todas las variables evaluadas con valores promedios de 330.22 cm, 66 cm, 33.88 cm, 0.81 y 6.81 m2 en altura de planta madre, fuste de planta madre, fuste de planta hijo, emisión foliar y área foliar respectivamente.
Keywords: FERTILIZANTES; FOLIARES; BANANO; CRECIMIENTO